Implementasi Kebijakan DIKLATPIM IV Pola Baru dalam Meningkatkan Kualitas Pelayanan Publik di Pemerintah Provinsi Gorontalo - Irfan Ibrahim (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2018)
The low quality of public services in government agencies becomes a challenge for all Autonomous Regions, especially the Regional Government of Gorontalo Province in increasing public satisfaction. Policy Implementation of Diklatpim IV Pola Baru is expected to increase the competence of Civil Servants in order to improve the quality of public service.This research was conducted in Gorontalo Province aims to know how influence of policy implementation of Diklatpim IV Pola Baru to public service quality.The research method uses quantitative design with explanatory method. Data collecting using questionnaire technique which 84 respondents obtained by stratified random sampling from population which amounted to 520 units.Data analysis using Partial Least Square (PLS) with SmartPLS 3.1 software to test the measurement model and to know the significance of Policy Implementation of Diklatpim IV Pola Baru to Quality of Public Service.The result showed that the loading factor of Policy Implementation of Diklatpim IV Pola Baru to Quality of Public Service was not significant at 5% because the value of T-Statistic under the value of t table 1,96. Similarly, the value of P-Value 0,546 higher than the value of significance P-Value <0.05 and coefficient value 7,9% only, so that the hypothesis H0 accepted, H1 rejected.Thus, it can be concluded that although the level of Policy Implementation of Diklatpim IV Pola Baru is high and the level of public service quality is also high but Policy Implementation of Diklatpim IV Pola Baru has no significant effect to the Quality of Public Service.